Minerals and Manpower - PRESIDENTIAL ADDRESS (The Southern African Institute of Mining and Metallurgy, 1974)
Minerals and Manpower - PRESIDENTIAL ADDRESS given by R. P. Plewman, Pr. Eng., B.Sc. (Eng) (Wits), M.A. (Oxon.) INTRODUCTION What I want to discuss is the future pattern of manpower in the mining industry, and I should like to begin by examining some relevant statistics. There are four areas that must be examined. Firstly, the future rate of production of different minerals must be estimated. Secondly, an assessment must be made of the balance of different mining technologies likely to be used for each mineral. Thirdly, the manpower requirements for each technology must be determined. And, fourthly, the future manpower resources of the country must be explored. NIM report Report No. 1646 Examination of the methods of analysis for calcium fluoride in fluorspar.